2018
DOI: 10.1186/s13002-018-0243-6
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the motivations for keeping wild birds in the semi-arid region of Brazil

Abstract: BackgroundBirds are kept as pets around the world, and bird-keeping is an ancient and widespread practice, constituting one of the main reasons for the decline of some species. In the semi-arid region of Brazil, this practice is very common and continues despite being designated as illegal in recent decades.This study aimed to identify the species and families of songbirds used as pets in the semi-arid region of Brazil, characterize the maintenance of the exploited species in captivity, and evaluate the socioc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 43 publications
3
23
0
2
Order By: Relevance
“…Our data corroborate the results of Fernandes-Ferreira et al [25] in a study on songbird trade in the state of Ceará, Brazil, where it was found that the value of a red-cowled cardinal P. dominicana ranged from US$ 1.72 for newly captured individuals to US$ 172.41 for an excellent singer reared in captivity. The red-cowled cardinal P. dominicana is among the species with the highest UVs in the present study and has also been highlighted as one of the most traded birds in other areas of northeast Brazil [20,23,25,27,51,53,78].…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Our data corroborate the results of Fernandes-Ferreira et al [25] in a study on songbird trade in the state of Ceará, Brazil, where it was found that the value of a red-cowled cardinal P. dominicana ranged from US$ 1.72 for newly captured individuals to US$ 172.41 for an excellent singer reared in captivity. The red-cowled cardinal P. dominicana is among the species with the highest UVs in the present study and has also been highlighted as one of the most traded birds in other areas of northeast Brazil [20,23,25,27,51,53,78].…”
Section: Discussionmentioning
confidence: 61%
“…The richness of bird species recorded is not surprising, as these animals are often kept as pets and are chosen because of their diversity of colors, song, ease of maintenance, and, in some cases, ability to imitate the human voice [49,50]. These factors have led to the preference of bird keepers for wild pets, especially Passeriformes [51][52][53][54][55] in the studied area, in other locations in Brazil, and worldwide. The main capture techniques mentioned by the interviewees in the researched area are widely used in other areas of the Brazilian semiarid [24,26,51] making it possible to capture a large number of species.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the species had UV g lower than one (1); nevertheless, four species had higher values, reflecting the local importance of these animals in the studied areas. Use value [ 37 39 ] is the most widely used technique among different researchers, and its results are generally interpreted as the possible use pressure on the species [ 40 43 ]. However, it does not distinguish between current use (effective) and potential use; therefore, the application of the UV g becomes unreliable for allocating a high number of potential uses in the analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Species with high use values (UV c and UV p ), such as S. bouveril, S. bouveril, S. flaveola, S. albogularis, S. nigricolis, and T. rufiventris, have been recorded with high general use values (UV g ) in several other studies of local populations in Northeast Brazil (Alves et al 2012(Alves et al , 2013aFernandes-Ferreira et al 2012;Loss et al 2014;Souto et al 2017;Oliveira et al 2018;Soares et al 2018b) and throughout the country (Regueira and Bernard 2012;Alves et al 2013b;Nascimento et al 2015). However, the simple application of UV g may emphasize species that are not being effectively used (UV c ).…”
Section: Discussionmentioning
confidence: 95%
“…(Sis-Fauna-169/2008;Sispass-10/2011). Nonetheless, as emphasized by Alves et al (2013b), Brazil has received abundant criticism for a variety of issues related to trade of wild birds, including abusive prices once there is no standardization on the prices and taxes involved in commercialization, exotic species, animal welfare, and cultural aspects (the use of birds in small fights "rinhas"), that motivate bird breeding and marketing (Alves et al 2010;Souto et al 2017;Oliveira et al 2018).…”
Section: Introductionmentioning
confidence: 99%